2011 XXXth URSI General Assembly and Scientific Symposium 2011
DOI: 10.1109/ursigass.2011.6051150
|View full text |Cite
|
Sign up to set email alerts
|

Testing of the backward wave oscillator model by using the spectral characteristics of VLF chorus elements

Abstract: A generation mechanism for chorus was suggested by Trakhtengerts (1995) on the basis of the backward wave oscillator (BWO) regime of the magnetospheric cyclotron maser. According to this model, step-like deformation on the electron distribution function is the most important factor of chorus generation, but such a feature is very difficult to observe. By measuring the frequency sweep rates in chorus elements detected by the Cluster spacecraft we determine the mean values and distributions of a dimensionless pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, using α = 72° brings the average agreement between the fitted value of Γ H and Γ OB within ∼3%. Similarly, the value of Q in the BWO model used above ( Q = 2) might also be underestimated; e.g., Titova et al [2011] suggested that, on average, Q ≈ 8 for lower band chorus calculated using observational frequency sweep rates. However, the exact value of α or Q should be determined through more rigorous numerical simulations and observed distribution functions.…”
Section: Comparison Between Theory and Observationmentioning
confidence: 99%
“…For example, using α = 72° brings the average agreement between the fitted value of Γ H and Γ OB within ∼3%. Similarly, the value of Q in the BWO model used above ( Q = 2) might also be underestimated; e.g., Titova et al [2011] suggested that, on average, Q ≈ 8 for lower band chorus calculated using observational frequency sweep rates. However, the exact value of α or Q should be determined through more rigorous numerical simulations and observed distribution functions.…”
Section: Comparison Between Theory and Observationmentioning
confidence: 99%